2022
DOI: 10.3390/biomedicines10092281
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Extracellular Vesicle-Based Therapies Using Induced Pluripotent Stem Cell-Derived Mesenchymal Stromal Cells

Abstract: Extracellular vesicles (EVs) are being widely investigated as acellular therapeutics in regenerative medicine applications. EVs isolated from mesenchymal stromal cells (MSCs) are by far the most frequently used in preclinical models for diverse therapeutic applications, including inflammatory, degenerative, or acute diseases. Although they represent promising tools as cell-free therapeutic agents, one limitation to their use is related to the batch-to-batch unreliability that may arise from the heterogeneity b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Assay of peritoneal lavage demonstrated that ihMSCs generated by VWB/GelMA-M, but not monolayer, was sufficient to inhibit several markers of inflammation. The lack of activity by monolayer ihMSCs is surprising because live cells and their secreted extracellular vesicles (EV) have been shown to inhibit inflammation in various studies [ 71 , 72 ], but the improved performance of VWB/GelMA-M ihMSCs could be attributable to microcarrier culture which can improve EV output and immune modulatory capacity [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Assay of peritoneal lavage demonstrated that ihMSCs generated by VWB/GelMA-M, but not monolayer, was sufficient to inhibit several markers of inflammation. The lack of activity by monolayer ihMSCs is surprising because live cells and their secreted extracellular vesicles (EV) have been shown to inhibit inflammation in various studies [ 71 , 72 ], but the improved performance of VWB/GelMA-M ihMSCs could be attributable to microcarrier culture which can improve EV output and immune modulatory capacity [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, our research group demonstrated that MSC-EVs re ect the characteristics of their originating cells, such as angiogenic properties in adipose-derived MSCs (ADMSCs) and chondrogenic effects in bone marrow-derived MSCs (BMSCs) (18). Consequently, MSCs derived from human iPSCs appear as a promising cell source for the manufacturing of MSC-EV therapeutics (29). Hence, we hypothesized that EVs derived from iMSCs could address these challenges and serve as a superior source for bone marrow derived-MSC-EVs for the treatment of osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Even though we established a novel culture medium that allows a longer culture of CMs, these cells should be transferred to bioreactor culture since, in general, EV recovery is very low and large quantities of medium are needed (Silva et al., 2021 ). Thus, CMs should be able to be adapted to novel culture conditions, and this process is challenging in primary culture cells (Bertolino et al., 2022 ; Silva et al., 2021 ). This is an essential step that should be addressed to bring this project to fruition.…”
Section: Discussionmentioning
confidence: 99%